Negotiating Foreignness Across the U.S.–Canadian Border: Narrating the Francoeur Family’s Everyday Life in David Plante’s The Family and The Native - Gaddas, Aya (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d’études canadiennes, 2011)
This article analyses David Plante’s novels The Family (1978) and The Native (1988), dealing with instances of Franco-American identity formation in the context of contemporary Providence, Rhode Island, and using the theme of foreignness to discuss the negotiation of cultural identity across the forty-ninth parallel. Plante’s characters dwell at the interstices of the abstract and the concrete, the foreign and the familiar, the global and the local, the borderless and the clear-cut. Immigration is seen in the context of a larger global movement of capital and labour across borders placed within contemporary discourses on globalization and an increasingly borderless world. The material realities within the borders of the parish in Providence are reset around Franco-American subjects as the Francoeur family navigates spaces and debates their cultural integration and social mobility within the adoptive country.